A multidisciplinary approach in the evaluation of patients with chronic renal disease. A narrative review - Bravo-Zúñiga, Jessica (2023)
Chronic renal disease (CRD) is an important public health problem. There is no a national renal health program in Peru. There is evidence that the multidisciplinary model of care in patients with CRD delays progression and reduces all-cause mortality. Although there is no agreement on certain topics, such as at which glomerular filtration rate should the multidisciplinary team work, it is clear that outcomes are improved. Human and financial resources are needed to implement this approach.